PHYSICS 110A : CLASSICAL MECHANICS

HW 3 SOLUTIONS

(1) Taylor 6.6
(a)
p
Here we are working with ds = dx2 + dy 2 . For a function y = y(x) we will pull out a dx
to have:
s 
2
q
p
dy
ds = dx2 + dy 2 = dx 1 +
= dx 1 + (y 0 )2 .
dx
(b)
Similarly for a function x = x(y) we have:
s 
2
q
p
dx
2
2
= dy 1 + (x0 )2 .
ds = dx + dy = dy 1 +
dy
(c)
Now for cylindrical coordinates we should remember the line element looks like:
d~l = drˆ
r + rdφφˆ + dz zˆ.
So for a function r = r(φ) we have:
s
p
ds = dr2 + r2 dφ2 = dφ 

r2

+

dr
dφ 

2

q
= dφ

r2 + (r0 )2 .

An alternate and equivalent way to do this is to begin from the Euclidean distance in (a)
and write x and y (and z, if needed) in the coordinate system you are transforming to. In
this case
x = r cos φ and y = r sin φ
so
dx =

∂x
∂r dr

+

∂x
∂φ dφ

= cos φdx − r sin φdφ

dy =

∂y
∂r dr

+

∂y
∂φ dφ

= sin φdx + r cos φdφ

in which case, after some algebra and use of basic trig identities (which you should go
through), we have
q
p
ds = (cos2 φ + sin2 φ)dr2 + r2 (cos2 φ + sin2 φ)dφ2 = dr2 + r2 dφ2
which recapitulates what we have above in a completely equivalent manner. This method is
often useful when you don’t know the specific measure or line element of a specific coordinate
system.

1

(g) So for a function θ = θ(φ) we have: s  2 q q dθ 2 2 2 2 2 2 ds = R dθ + R sin θdφ = Rdφ sin θ + = Rdφ sin2 θ + (θ0 )2 .(d) And for a function φ = φ(r) we have: s p ds = dr2 + r2 dφ2 = dr  1+ r2 1+ R2 dφ dr 2 q = dr 1 + r2 (φ0 )2 . (f ) For a function z = z(φ) we have: s ds = p dz 2 + R2 dφ2  R2 = dφ + q = dz R2 + (z 0 )2 .11 We want to find the path y = y(x) for which the integral: Zx2 √ p x 1 + y 02 dx. (2) Taylor 6. (e) For a function φ = φ(z) we have: s p ds = dz 2 + R2 dφ2 = dz  dφ dz 2 dz dφ 2 q = dz 1 + R2 (φ0 )2 . x1 is stationary. For this we turn to the Euler-Lagrange equation: ∂f d ∂f − = 0. Finally for spherical coordinates we have: ˆ d~l = drˆ r + rdθθˆ + r sin θdφφ. ∂y dx ∂y 0 2 (1) . dφ (h) And for a function φ = φ(θ) we have: q ds = R2 dθ2 + R2 sin2 θdφ2 = Rdθ s 2  1 + sin θ dφ dθ 2 = Rdθ q 1 + sin2 θ (φ0 )2 .

Where f = √ p x 1 + y 02 . 0 A hint is given to change this into the form: Zl Area = f ds. 4k 2 (3) Taylor 6. 1 + y 02 Solving for y 0 we have: k . So this leads us to an equation for a parabola as such: x= (y + C)2 + k2 . √ Where C = 2k x0 − k 2 + y0 . ∂f As f is not explicitly dependent on y we have ∂y 0 = constant or: √ 0 xy p = k.22 The equation to find the area between the string and the x-axis is as so: Zxf Area = ydx. x − k2 Which has the solution: y = 2k p x − k 2 − C. (2) 0 so that we can deal with something we know. the length of the string. Our normal ds element is as such: ds = p dx2 + dy 2 . . l. x − k2 Which is a separable differential equation which can be solved like: y0 = √ Zx dy = dx √ x0 k . Which can be rearranged to get: s p dx = ds2 − dy 2 = ds 1− 3 dy 2 = ds ds q 1 − y02.

∂y 0 f − y0 Which for us will be: y p 1 − y02 = k. Which is the equation of a circle with radius k. Now since there is no explicit dependence on s in f we can use the ’first integral’ as in equation 6. This in turn leads to: y0 = p 1 − (y/k)2 . Where k is some constant. (3) Now we can go back to out definition of dx from above: q dx = ds 1 − y 0 2 . Integrating this we have: arcsin(y/k) = s/k. (4) Putting equation 3 and 4 together we have: (x − k)2 + y 2 = k 2 .43 of the text. Integrating this we get: x = k − k cos(s/k). 4 . v si For us ds will be: q p 2 2 ds = dx + dy = dx 1 + y 0 2 . (4) Taylor 6. So we will have: ∂f = constant. If we use the boundary conditions y(s = 0) = y(s = `) = 0 and x(s = 0) = 0 we obtain k = π` .This will give us an f in equation 2 above of: q f = y 1 − y02. or: y = k sin(s/k).23 The integral for time takes the form: Zsf t= ds .

2 and. (v0 cos φ + V y)2 + v02 sin2 φ are small we can approximate: q 1 2 ds = dx 1 + y 0 2 ≈ dx(1 + y 0 ). So we have: Zxf t= xi Here our functional is: dx(1 + 12 y 0 2 ) . 1 + ky 1 + ky 1 + ky This is a first order differential equation. v0 (1 + ky) 1 + 21 y 0 2 . 2 Or: 1 1 − λ2 D2 − 2λ2 x2 + 2λ2 Dx = C + Ck[λxD − λx2 ]. Matching the x2 coefficients requires C = 2λ k . ∂y 0 For us this looks like so: 1 − 21 y 0 2 1 + 21 y 0 2 y02 − = = C. So we have: Zxf t= xi Now when φ and y0 dx p 1 + y02 q . v ≈ v0 + V y. f= 1 + ky Now this is not explicitly dependent on the variable x so we may use the ’first integral’ as we discussed in discussion section Thursday night but did not finish. The first integral is as follows: f − y0 ∂f = C. Now we are told the solution looks as follows: y = λx(D − x). (5) 2 We get an equation for λ by matching coefficients of each power of x on either side of the 0 equations. There is a subtlety. Plugging in to our differential equation we get: 1 2 1 − y 0 = C(1 + ky).And the velocity v is: q v = (v0 cos φ + V y)2 + v02 sin2 φ. Then matching the constant (x ) term requires 1 2λ 1 − λ2 D 2 = . however. 2 k 5 .

25 Let’s start by stating the parameterized equation for x and y: x = a(θ − sin θ). The book suggests a change of variables θ = π−2α. You may also do this using the Euler-Lagrange equation (equation 1) to get a second order differential equation: k y 00 [1 − ky] + k − y 02 = 0. And we can find the velocity using conservation of energy: p p v = 2g(y − y0 ) = 2ga(cos θ0 − cos θ). Where we inserted the above definition for x and where y0 = a(1 − cos θ)(remember in this picture gravity is in the positive y-direction). and y = a(1 − cos θ). p √ (a(1 − cos θ))2 + (a sin θ)2 = a 2 − 2 cos θ. g 2ga(cos θ0 − cos θ) (cos θ0 − cos θ) p a 2(1 − cos θ) θ0 So now we have this integral to complete.Which has solution: √ λ= 4 + 2k 2 D2 − 2 . With this change we can find: 6 . Putting this together with our definition of time integral we have: Zsf t= si ds = v Zπ θ0 p r Zπ (1 − cos θ) a dθ p = dθ p . (5) Taylor 6. 2 This will lead to the same equation for λ. Now the differential is ds = p dx2 + dy 2 or: p ds = dx2 + dy 2 = dθ So: ds = s dx dθ 2  + dy dθ 2 . kD2 as advertised.

the extra distance the car needs to travel is exactly balanced by the increased slope of the track. t=2 dα p g (sin2 α0 − sin2 α) 0 Let’s do a substitution u = sinα sin α0 : r Z1 r r du a aπ a √ t=2 =2 =π . Qualitatively if you were to move the car’s initial position further up the track. 7 . 2 g g2 g 1−u 0 So this means no matter where you let go of the car.r Zα0 a cos α . the time to get to the bottom is the same. which gives the car greater velocity more quickly.